BRAINSTORMING TECHNIQUE TO IMPROVE WRITING SKILL IN DESCRIPTIVE TEXTS OF VOCATIONAL HIGH SCHOOL STUDENTS - Candra Minawati (English Education Department Slamet Riyadi University Surakarta, 2018)
The article was based on a research that concerned in improving students’ skill in writing descriptive texts using Brainstorming Technique. The objectives were: 1) To find out whether the use of Brainstorming Technique can improved the writing skill in descriptive texts of tenth grade students of SMK Plus Bhakti Oetama Gondangrejo in the academic year of 2017/2018, and 2) To d e s c r i b e t h e c l a s s c o n d i t i o n w h e n brainstorming technique were implemented in writing skill in descriptive texts of tenth grade students of SMK Plus Bhakti Oetama Gondangrejo in the academic year of 2017/2018. The researcher wa s conducted in c l a s s X wh i c h c o n s i s t e d o f 3 0 f e ma l e s t u d e n t s from August to September 2017. This Classroom Action Research (CAR) consisted of 2 cycles. Each cycle consisted of two meetings in 80 minutes for each meeting. The data were collected through test and non-test. The tests consisted of pre-test and post-tests. While, non-tests consisted of observation, interview, field notes and documentation. Furthermore, the researcher used qualitative and quantitative data analysis to analyze the data. The result of this research showed that Brainstorming Technique could improve the students’ skill in writing descriptive texts at the tenth grade students especially class X of SMK Plus Bhakti Oetama Gondangrejo. The improvement could be seen from the result of the test. The mean score of pre-test was 4.80, post-test 1 was 6.93, and post-test 2 was 7.68. Moreover, the result of t-test was 12.321 in cycle 1 and 3.425 in cycle 2. It meant that there was improvement in students’ skill in writing descriptive texts. Key words: Writing Skill; Descriptive Texts; Brainstorming Technique; Classroom ActionResearch